Contribution of forest plantations to soil phosphorus reserves - Giannini, Ana Paula; Restovich, Silvina Beatriz; Lupi, Ana Maria; Ferrere, Paula; Beribe, Maria Jose (National Scientific Society, 2024)
Poster y resumen